2016
DOI: 10.1016/j.tet.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of diphenylacetylene using Al powder in the presence of noble metal catalysts in water

Abstract: Diphenylacetylenes can be reduced to the corresponding diphenylethanes (2) in water in excellent yield using Al powder and Pd/C at 60 °C for 3 h in a sealed tube. In addition, the complete reduction of both aromatic rings required 80 °C for 15 h with Al powder in the presence of Pt/C. However, the nature of hydrogenated product formed was found to be strongly influenced by the reaction temperature, time, volume of water and the amount of catalyst being employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Since the mechanistic study revealed that the indoline/ t -BuOK/O 2 reaction system could generate a potent electron donor ( Int-3 ) in situ , we sought to exploit its potential use in single electron reduction. A preliminary study showed that this system is able to promote a series of reduction and reductive cleavage reactions ( Scheme 6 ), such as the reduction of benzophenone ( 6 ) 18 and diphenylacetylene ( 8 ), 19 as well as the reductive cleavage of diphenylsulfone ( 10 ) 20 and benzyl trityl ether ( 11 ). 21 These reactions traditionally required the use of potent single electron reductants ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Since the mechanistic study revealed that the indoline/ t -BuOK/O 2 reaction system could generate a potent electron donor ( Int-3 ) in situ , we sought to exploit its potential use in single electron reduction. A preliminary study showed that this system is able to promote a series of reduction and reductive cleavage reactions ( Scheme 6 ), such as the reduction of benzophenone ( 6 ) 18 and diphenylacetylene ( 8 ), 19 as well as the reductive cleavage of diphenylsulfone ( 10 ) 20 and benzyl trityl ether ( 11 ). 21 These reactions traditionally required the use of potent single electron reductants ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the GC-MS analysis, a reaction pathway for the reduction of phenylacetylene can be proposed. 47 The reduction of triple bond to a single bond directly in pathway 1 and the single bond is afforded via the intermediate styrene (2) as shown in pathway 2. The intermediate compound 2 only forms when Pd/C is used with Al powder (Table 1; entry 5) and the mixture of Raney Ni-Al alloy with Pt/C (Table 3; entry 2) under mild reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[86] Retro-reductive aminations followed by direct transformations of amines to ketones with Pd/C in water under microwave irradiation have been reported by Tashiro et al [142,143], and this is shown in fig 3. and the following reaction pathways have been suggested [146]. Reduction of aniline can be carried out with noble metal catalysts in the presence of Al powder in water to the corresponding cyclohexane derivatives.…”
Section: Plausible Reaction Mechanism For Benzophenonementioning
confidence: 99%